EVALUASI SISTEM DRAINASE DI KAWASAN PEMUKIMAN PENDUDUK WILAYAH KAMPUNG IRIAN KELURAHAN SEKETENG KABUPATEN SUMBAWA - Adinda Srivangga; Adi Mawardin (Program Studi Teknik Sipil, Fakultas Teknik Universitas Teknologi Sumbawa, 2024)
Jalan Tongkol area, Seketeng District, Sumbawa Regency, NTB. This is a road frequently used by residents. The drainage channel on Jalan Tongkol, Seketeng District, is unable to withstand the flow of air during heavy rain. This writing aims to analyze the feasibility of existing channel dimensions and identify the causes of the current accumulation of air conditions. This study was carried out by carrying out hydrological and hydraulic analysis. Hydrological analysis includes rainfall data, rain intensity using the Mononobe formula and flood discharge using the Rational formula. Next, calculate the flood discharge by expanding the Catchment Area area, the flow coefficient value and the rain intensity during the concentration time using the equation Tc=Td+To. The rainfall value used to calculate rainfall intensity is the average maximum daily rainfall value from 2011 to 2020 at the BBMKG Station in the Sultan Kaharuddin area, Sumbawa Besar.